Polynomial tempered distributions - Sharyn, S.V. (Carpathian Mathematical Publications, 2010)
In the article, polynomial (nonlinear) analogue of tempered Schwartz distributions is constructed. Generalized operation of differentiation in the space of polynomial generalized functions as well as Fourier-Laplace transformation of such distributions are considered. Some examples are given.